2005
DOI: 10.1111/j.1538-7836.2005.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

High functional levels of thrombin-activatable fibrinolysis inhibitor are associated with an increased risk of first ischemic stroke

Abstract: Summary. Background and objective: Several studies have suggested that thrombin-activatable fibrinolysis inhibitor (TAFI) levels are associated with the risk of arterial thrombosis, but results have been contradictory. We studied functional TAFI levels and TAFI gene polymorphisms in 124 patients with a recent ischemic stroke and 125 age-and sex-matched controls to establish the role of TAFI in ischemic stroke. Methods and results: Functional TAFI levels, defined as TAFI-related retardation (RT), the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 25 publications
5
96
2
Order By: Relevance
“…view of this, it is of interest that there is a recent study reporting increased plasma levels of functional TAFI in acute ischemic stroke. 22 However, ischemic stroke is a highly heterogeneous disorder, and as this study included only approximately 120 patients, it was not possible to study the association between TAFI and ischemic stroke subtypes.Here we aimed to perform a comprehensive investigation of the possible association between ischemic stroke and TAFI among participants in the Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS), in which ischemic stroke subtype has been determined by Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. 23 To this end, TAFI was analyzed at the protein level by 2 newly developed immunologic assays with distinct reactivities, recognizing either intact TAFI or the released AP, 24 and, at the genetic level, by a selection of tagging SNPs over the TAFI locus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…view of this, it is of interest that there is a recent study reporting increased plasma levels of functional TAFI in acute ischemic stroke. 22 However, ischemic stroke is a highly heterogeneous disorder, and as this study included only approximately 120 patients, it was not possible to study the association between TAFI and ischemic stroke subtypes.Here we aimed to perform a comprehensive investigation of the possible association between ischemic stroke and TAFI among participants in the Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS), in which ischemic stroke subtype has been determined by Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. 23 To this end, TAFI was analyzed at the protein level by 2 newly developed immunologic assays with distinct reactivities, recognizing either intact TAFI or the released AP, 24 and, at the genetic level, by a selection of tagging SNPs over the TAFI locus.…”
mentioning
confidence: 99%
“…The finding of increased plasma levels of TAFI in overall ischemic stroke is in agreement with 3 previous studies, despite somewhat different study designs. 22,30,31 Montaner et al showed that TAFI Ag levels, measured within 24 hours of onset of the event, were increased in a small sample (nϭ30) of elderly ischemic stroke patients. 31 Santamaría et al investigated 114 young (mean age 56 years) patients with ischemic stroke or transient ischemic attacks.…”
mentioning
confidence: 99%
“…Additionally, TAFI may also help the growth and spread of tumor cells owing to the accumulation of intra-tumor fibrin and activation of the blood coagulation system (Fidan et al, 2012). TAFI is important in CCVDs, such as coronary heart disease, angina pectoris, ischemic stroke, myocardial infarction, and venous thrombosis, mainly owing to its role in thrombosis treatment (Zorio et al, 2003;Leebeek et al, 2005;Tokgoz et al, 2013). Polymorphisms of the CPB2 gene result in changes in the amino acid sequence and function of TAFI, especially in the molecular stability of TAFIa and its anti-fibrinolytic activity in arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…An additional study was removed owing to a lack of data integrity. Ultimately, we obtained nine case-control research papers published between 2003 and 2013 that were of moderate-to-high quality (Zorio et al, 2003;Leebeek et al, 2005;Xu et al, 2008;Biswas et al, 2009;Si, 2010;Kamal et al, 2011;Shi et al, 2011;Sun et al, 2011;Tokgoz et al, 2013). The demographic information, baseline characteristics, and other features, and the methodological quality of the extracted studies are presented in Tables 1 and 2.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation